Números inteiros e suas operações: uma proposta de estudo para alunos do 6º ano com o auxílio de tecnologia - Souza, Flávio Cabral de (2015)
The aim of this paper was to assess how students at sixth grade of elementary school in Brazil, who have never had any formal contact with integers numbers and operations, use their prior knowledge to solve situations involving this mathematical object and how they develop their knowledge autonomously. To achieve this goal, a review of the literature was made in order to check how researchers have treated the integers numbers and which strategies for the approach of integers numbers and their operations were used in the past. This review was crucial to develop activities that allowed the students to engage with problem solving and to bring out their prior knowledge. The series of activities developed for this project included visual resources with the aid of technology, problem situation and objective questions. During the development of the activities, it was possible to identify, through the records and conversations in the classroom, the singularities related to the understanding of integers numbers and their operations by the students. Therefore, this research has identified the scope of the students prior knowledge in the understanding of integers numbers and their operations, and the obstacles they faced when addressing this content. The results of this project can help us to rethink how integers numbers and their operations can be addressed in the teaching practice